Publishing the results: beware of "predatory" publishers - Hall, Robyn; Nelson, Jody (My University, 2018)
Learn how to identify and avoid questionable academic journal publishing practices.
Presented on November 28, 2018 at the R & S Lunch & Learn held at MacEwan University in Edmonton, Alberta.
Keywords: open access; academic publishing; journals; nursing